2004
DOI: 10.1046/j.8755-8920.2003.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with Dendritic Cells Influences the Spontaneous Resorption Rate in the CBA/J × DBA/2J Mouse Model

Abstract: Syngeneic DC prevented abortions and this was linked to a decrease in IL-6 levels, but not with levels of asymmetric antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 45 publications
5
38
0
Order By: Relevance
“…The interpretation that GM-CSF facilitates an appropriate T cell response to pregnancy is consistent with experiments showing that administration of exogenous GM-CSF in the preimplantation period can normalize fetal loss rates in abortion-prone CBA 3 DBA/2 mice and is associated with expansion of CD8 + T cells with suppressive function (68). Administration of bone marrow-derived DCs from normal fertile mice to abortion-prone CBA 3 DBA/2 mice similarly reduces the miscarriage rate, implying that GM-CSF-mediated rescue of fetal loss is operating through a DC-mediated mechanism (69).…”
Section: Cd11cmentioning
confidence: 93%
“…The interpretation that GM-CSF facilitates an appropriate T cell response to pregnancy is consistent with experiments showing that administration of exogenous GM-CSF in the preimplantation period can normalize fetal loss rates in abortion-prone CBA 3 DBA/2 mice and is associated with expansion of CD8 + T cells with suppressive function (68). Administration of bone marrow-derived DCs from normal fertile mice to abortion-prone CBA 3 DBA/2 mice similarly reduces the miscarriage rate, implying that GM-CSF-mediated rescue of fetal loss is operating through a DC-mediated mechanism (69).…”
Section: Cd11cmentioning
confidence: 93%
“…Kammerer et al described the presence of subpopulations of DC in decidual tissue during the early phase of human pregnancy which seem to participate in the protection of the allogeneic fetus in a mouse pregnancy model. [81][82][83] Using in vitro models we could oberve that those DC differentiated from CD14C cells from fertile women and co-cultured with trophoblast cells prevented the up-regulation of CD83 expression, a maturation marker after a challenged with LPS. 84 In fact, they did not modulate the expression of CD86, CD40 and HLA-DR suggesting that DCs remained in a semi-mature state.…”
Section: Differential Migration and Activation Profile Of Dendritic Cmentioning
confidence: 99%
“…In fact, CCR7 interfered with accumulation of Tregs in the uterus and implantation indicating that homing of Tregs to the uterus was mediated by CCR7. 82 Endometrial stromal cells under the decidualization program differentiate into epithelioid decidual cells and secrete diverse mediators, contributing to the generation of a local immune response supporting the nidation of a semiallogenic fetus. 83,84 Using an in vitro model of decidualization with a human endometrial stromal cell line (HESC) stimulated with P4 and LPS simulating the inflammatory response during implantation, we observed that P4 increased VIP intracellular production in a concentration dependent manner.…”
Section: Induction and Migration Of Maternal Tregs Cellsmentioning
confidence: 99%
“…25 Mouse BM-derived DCs (BMDCs) were obtained from C57Bl/6J femurs and tibias and cultured in IMDM (GIBCO-BRL) containing 10% FCS and 30% GM-CSF-containing J558 conditioned medium, prepared as described previously. 26 BMDCs were routinely checked for purity and maturation markers by flow cytometry. OT-1 CD8 ϩ T cells were isolated from lymph node and spleen suspensions of OT-1 mice.…”
Section: Cellsmentioning
confidence: 99%